2019
DOI: 10.1108/cms-03-2019-0115
|View full text |Cite
|
Sign up to set email alerts
|

Initial entry speed and international performance of INVs

Abstract: Purpose In the literature concerning international new ventures (INVs), there has been a tension between the learning advantages of newness and absorptive capacity perspectives for explaining the performance influence of initial entry speed. To address this tension, this paper, through integrating both the motivation and ability to acquire foreign knowledge, proposes a theoretical model about the nonlinear relationship between INVs’ initial entry speed and international performance. Drawing upon upper echelons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 99 publications
(182 reference statements)
0
1
0
Order By: Relevance
“…However, firm size and firm age at internationalization and market liberalization were not significantly related to international performance in all models. This is because: international perfor-mance relies more on resource orchestration rather than resource possession (Sirmon et al, 2011) indicated by firm size; firm age at internationalization has a positive effect on the motivation but a negative impact on the ability to acquire foreign knowledge (Huang, Ye and Shen, 2020); market liberalization also has both positive and negative effects on firm performance (Chang and Wu, 2014).…”
Section: Hypothesis Testing: Main Effects and Moderating Effectsmentioning
confidence: 99%
“…However, firm size and firm age at internationalization and market liberalization were not significantly related to international performance in all models. This is because: international perfor-mance relies more on resource orchestration rather than resource possession (Sirmon et al, 2011) indicated by firm size; firm age at internationalization has a positive effect on the motivation but a negative impact on the ability to acquire foreign knowledge (Huang, Ye and Shen, 2020); market liberalization also has both positive and negative effects on firm performance (Chang and Wu, 2014).…”
Section: Hypothesis Testing: Main Effects and Moderating Effectsmentioning
confidence: 99%